Guidelines for the implementation of a training program in Personalized Bioethics addressed to university teachers - Guzmán Avalos, Magna (2018)
Currently university education requires that the teacher has a comprehensive education, which implies having teachers with positive qualities that not only transmit knowledge on the academic aspect, scientific-technological development or social responsibility, but these, in addition to Their professional development must have a vocation for service, as well as a solid moral, ethical and bioethical training, capable of transmitting principles and values, that is, being a living example of what they say, considering the student as a person in all its context. In this article we have identified the guidelines for the implementation of a personalist bioethics training program aimed at university professors, for which the current situation of university teacher training in bioethics in Peru has been defined, as well as the contents bioethics that should be considered in the training of university professors, having as a transversal axis of their contents the personalist bioethics. The conclusions reached is that, the current situation of the university teacher requires a rigorous comprehensive training, including personalist bioethics for the role of trainer that performs, promoting its progressive implementation in university education plans, at the level of undergraduate and postgraduate. The guidelines to be implemented are: human person, human dignity, integrity of the person and person integrity, value of human life in all its stages, value of human sexuality, freedom and respect, sociability and socialization.